1991
DOI: 10.1093/jac/28.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue penetration of rufloxacin, a long acting quinolone antimicrobial agent

Abstract: The pharmacokinetics of rufloxacin after a single 400 mg oral dose were studied in eight volunteers, measuring plasma, inflammatory fluid and urine concentrations. Mean peak plasma concentrations of 4.4 mg/L were achieved at a mean time of 1.9 h after administration. The mean plasma elimination half-life was 28.2 h. Mean peak levels in inflammatory fluid reached 3.2 mg/L after 3.5 h, and 30.7% of the dose was eliminated in urine by 96 h. The apparent mean volume of distribution of rufloxacin, at steady state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
29
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 0 publications
6
29
0
Order By: Relevance
“…Rufloxacin is administered orally and displays a long half-life in plasma (28 to 30 h), consistently high bactericidal concentrations at the site of infection, and good penetration into infected tissues and cerebrospinal fluid (24,31). To evaluate the intraocular penetration and therapeutic benefit of rufloxacin, whether delivered by TSP or not, an experimental model of P. aeruginosa and S. aureus keratitis in rabbits was developed; the drug efficacy was then compared with that of ofloxacin, which is commonly used for the topical therapy of this ocular pathology (13,26,29).…”
mentioning
confidence: 99%
“…Rufloxacin is administered orally and displays a long half-life in plasma (28 to 30 h), consistently high bactericidal concentrations at the site of infection, and good penetration into infected tissues and cerebrospinal fluid (24,31). To evaluate the intraocular penetration and therapeutic benefit of rufloxacin, whether delivered by TSP or not, an experimental model of P. aeruginosa and S. aureus keratitis in rabbits was developed; the drug efficacy was then compared with that of ofloxacin, which is commonly used for the topical therapy of this ocular pathology (13,26,29).…”
mentioning
confidence: 99%
“…(15). It has excellent serum and urine concentrations and a particularly long half-life (35 h) with a slow renal elimination, allowing for once-a-day administration (11,16,39). The plasma and urine half-lives of rufloxacin are two times longer than those of pefloxacin (4,23).…”
mentioning
confidence: 99%
“…In vitro, the antibacterial activity of rufloxacin is similar to that of norfloxacin (36), while in animal models it has activity similar to that of ciprofloxacin (12). In humans pharmacokinetic studies have demonstrated that rufloxacin is eliminated slowly, with a half-life in plasma of about 35 h (14,19,37). The drug penetrates well into most body fluids, tissues, and cells, where it reaches high and stable concentrations, ranging from 2 to 25 times those in plasma (4,19,35,37).…”
mentioning
confidence: 99%